Effect of Sugar On Dried-Spiced Fish Fillets Processing to The Quality - Eko Nurcahya Dewi; Ratna Ibrahim (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2006)
“Dendeng ikan” (dried-spiced fish fillets) is a traditionally processed fish product in Indonesia involving spicing and drying process. In terms of the quality the product has some problems such as the quality is not satisfying yet, the product contains highly palm sugar which cause the colour is too brown and the product is easily to be burn when it is fried, the taste is very sweet, the moisture content of the product is relatively  high.  Some  people  like  sweet  taste of  fish  product  but  some  do  not.  The  experiment  was conducted in order to find out the data on the effect of using the mixture of granulated sugar and palm sugar (1:1) and sorbitol on “dendeng ikan” processing to the preference value and moisture content of the product. The results showed that the mixture of granulated sugar and palm sugar (1:1) and sorbitol used on “dendeng ikan” processing did not affect significantly to the preference value of fried “dendeng ikan”. However, it caused the moisture content of the products differ significantly (P<0,05).   Key words : “Dendeng ikan”, dried-spiced fish fillets, preference value, moisture content